PERAN APARATUR SIPIL NEGARA SEBAGAI KEPALA LINGKUNGAN TERHADAP PELAYANAN MASYARAKAT DI KELURAHAN RANOMUUT PADA MASA PANDEMI COVID 19 - Inggrit , Sumilat; Elfie ., Mingkid; Shirley Y. V. I Goni (Sam Ratulangi University, 2021)
This study aims to determine and analyze why the role of the state civil apparatus as the Head of Neighbourhood in Ranomuut Village in providing services to the community has not been as expected. Sources of data used are primary data and secondary data collected by researchers to support the first data. Interviews were conducted on 14 informants. The data analysis technique used includes transcripts of interview results, data reduction, analysis, data interpretation and triangulation and the method used is descriptive research method. The results showed that the performance in services to the community carried out by the State Civil Apparatus, in this case the head of the neighbourhood was not optimal and only one indicator that was carried out by the head of the environment was good, namely the relationship with the organization, where it was found that the head of the environment had a good relationship with the existing organization. this is proven by the cooperation between the head of neighbourhood and the employees with the service of the community properly and the employees can help the head of the neighbourhood in terms of explaining the management of population administration.